PENGARUH PENGGUNAAN BAHAN AJAR FLIPBOOK PADA PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR KIMIA KELAS XI DI MAS TI BATANG KABUNG - Rahmi Artika; Ulfia Rahmi; Septriyan Anugrah; Alkadri Masnur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was conducted to determine the effect of using Flipbook teaching materials in the implementation of the Problem Based Learning (PBL) model on the chemistry learning outcomes of grade XI students at MAS TI Batang Kabung. The results showed that the average learning score of students in the experimental class using Flipbook with the PBL model was 79.72, while that of the control class was 64.31. Based on the t-test analysis, the calculated t-value (????ₕᵢₜᵤₙ????) was 4.0641 and the table t-value (????ₜₐ????ₑ????) was 2.032 at a significance level of 0.05, indicating that ????ₕᵢₜᵤ???????? > ????ₜₐ????ₑ????. Therefore, it can be concluded that the use of Flipbook teaching materials in the application of the Problem Based Learning model has a significant effect on students’ chemistry learning outcomes. The use of Flipbook has been proven to help students become more motivated, active, and better understand the material, thereby positively impacting their learning achievement.